KEWENANGAN PEMERINTAH KOTA PEKANBARU DALAM PENANGANAN KAWASAN KUMUH TAHUN 2019-2020 - Muhammad Ilham (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Population growth in urban areas, especially in Kota Pekanbaru, continues to show an increase. Along with the population growth, the need for proper housing will of course increase. However, not all people can afford to have a decent house. This is what causes slum settlements in Pekanbaru City. Therefore, the purpose of this study is to determine the authority of the Pekanbaru City Government in handling slum areas in 2019 - 2020. As well as knowing the obstacles in handling slum areas in 2019 - 2020. The method used in writing this study is a qualitative approach, with the number of key informants. as many as 3 people. The results of this study indicate that the authority given to the Dinas is in the form of supervision and control, as well as community empowerment and community empowerment. 2. Constraints in the implementation of the slum eradication program, including: refusal by the community, community involvement in the KOTAKU program has not fully supported the implementation of the objectives of the program, the socio-economic conditions of the community and the level of technological progress, financial limitations, differences in education levels, employment / tribal professions and so on.  Keywords: Authority, Slum Settlement, KOTAKU, Pekanbaru.